Signatures of quiet Sun reconnection events in Ca ii, Hα, and Fe i. Issue 3 (18th June 2018) - Shetye, J; Shelyag, S; Reid, A L; Scullion, E; Doyle, J G; Arber, T D
ABSTRACT: We use observations of quiet Sun (QS) regions in the Hα 6563 Å, Ca ii 8542 Å,  and Fe i 6302 Å lines. We observe brightenings in the wings of the Hα and Ca ii combined with observations of the interacting magnetic concentrations observed in the Stokes signals of Fe i . These brightenings are similar to Ellerman bombs (EBs), i.e. impulsive bursts in the wings of the Balmer lines that leave the line cores unaffected. Such enhancements suggest that these events have similar formation mechanisms to the classical EBs found in active regions, with the reduced intensity enhancements found in the QS regions due to a weaker feeding magnetic flux. The observations also show that the quiet Sun Ellerman bombs are formed at a higher height in the upper photosphere than the photospheric continuum level. Using simulations, we investigate the formation mechanism associated with the events and suggest that these events are driven by the interaction of magnetic field lines in the upper photospheric regions. The results of the simulation are in agreement with observations when comparing the light curves, and in most cases, we found that the peak in the Ca ii 8542 Å wing occurred before the peak in Hα wing. Moreover, in some cases, the line profiles observed in Ca ii are asymmetrical with a raised core profile. The source of heating in these events is shown by the MURaM simulations and is suggested to occur 430 km above the photosphere.